ANTITHROMBOTIC THERAPY IN ELDERLY AND SENILE AGE: AN EXPERT CONSENSUS - O. N. Tkacheva; N. K. Runikhina; N. M. Vorobiova; A. L. Komarov; Yu. V. Kotovskaya; E. P. Panchenko; E. V. Plokhova; E. V. Frolova; I. S. Yavelov (Кардиоваскулярная терапия и профилактика, 2017)
.